Influence of sex on the age‐related adaptations of neuromuscular function and motor unit properties in elite masters athletes. (22nd October 2020) - Piasecki, Jessica; Inns, Thomas B.; Bass, Joseph J.; Scott, Reece; Stashuk, Daniel W.; Phillips, Bethan E.; Atherton, Philip J.; Piasecki, Mathew
Abstract : Key points: Masters athletes maintain high levels of activity into older age and allow an examination of the effects of aging dissociated from the effects of increased sedentary behaviour. Evidence suggests masters athletes are more successful at motor unit remodelling, the reinnervation of denervated fibres acting to preserve muscle fibre number, but little data are available in females. Here we used intramuscular electromyography to demonstrate that motor units sampled from the tibialis anterior show indications of remodelling from middle into older age and which does not differ between males and females. The age‐related trajectory of motor unit discharge characteristic differs according to sex, with female athletes progressing to a slower firing pattern that was not observed in males. Our findings indicate motor unit remodelling from middle to older age occurs to a similar extent in male and female athletes, with discharge rates progressively slowing in females only. Abstract: Motor unit (MU) remodelling acts to minimise loss of muscle fibres following denervation in older age, which may be more successful in masters athletes. Evidence suggests performance and neuromuscular function decline with age in this population, although the majority of studies have focused on males, with little available data on female athletes. Functional assessments of strength, balance and motor control were performed in 30 masters athletes (16 male) aged 44–83 years. Intramuscular needle electrodes were used to sample individual motor unit potentials (MUPs) and near‐fibre MUPs in the tibialis anterior (TA) during isometric contractions at 25% maximum voluntary contraction, and used to determine discharge characteristics (firing rate, variability) and biomarkers of peripheral MU remodelling (MUP size, complexity, stability). Multilevel mixed‐effects linear regression models examined effects of age and sex. All aspects of neuromuscular function deteriorated with age ( P < 0.05) with no age × sex interactions, although males were stronger ( P < 0.001). Indicators of MU remodelling also progressively increased with age to a similar extent in both sexes ( P < 0.05), whilst MU firing rate progressively decreased with age in females ( p = 0.029), with a non‐significant increase in males ( p = 0.092). Masters athletes exhibit age‐related declines in neuromuscular function that are largely equal across males and females. Notably, they also display features of MU remodelling with advancing age, probably acting to reduce muscle fibre loss. The age trajectory of MU firing rate assessed at a single contraction level differed between sexes, which may reflect a greater tendency for females to develop a slower muscle phenotype. Key points: Masters athletes maintain high levels of activity into older age and allow an examination of the effects of aging dissociated from the effects of increased sedentary behaviour. Evidence suggests masters athletes are more successful at motor unit remodelling, the reinnervation of denervated fibres acting to preserve muscle fibre number, but little data are available in females. Here we used intramuscular electromyography to demonstrate that motor units sampled from the tibialis anterior show indications of remodelling from middle into older age and which does not differ between males and females. The age‐related trajectory of motor unit discharge characteristic differs according to sex, with female athletes progressing to a slower firing pattern that was not observed in males. Our findings indicate motor unit remodelling from middle to older age occurs to a similar extent in male and female athletes, with discharge rates progressively slowing in females only.